Dissolved Oxygen Budget for Paciﬁc White Shrimp (Litopenaeus vannamei) Culture in Earthen Ponds - Anongponyoskun, Monton; Choksuchart, Apiradee; Salaenoi, Jintana; Aranyakananda, Porcham (Agriculture and Natural Resources, 2012)
Dissolved oxygen (DO) is one of the important factors which affect the quantity and quality of Paciﬁ c white shrimp (Litopenaeus vannamei) grown under intensive culture in earthen ponds. The aim of this research was to develop a model of the dissolved oxygen budget for shrimp culture for 5 mth during May to September 2009 (the ﬁ rst month for water preparation, the other months for nurture). The method was based on the conservation of mass. Empirical experiments were used to consider: 1) water oxygen production, 2) aeration by paddle wheel and 3) oxygen uptake in sediment, shrimps and water. The oxygen uptake in sediment increased each month, with a range of 0.03–0.11 mg.L-1.hr-1. The oxygen production and oxygen consumption by water were highest in the third month, and decreased in the fourth and ﬁ fth months, with a range of 0.13–0.51 and 0.06–0.33 mg.L-1.hr-1, respectively. Oxygen consumption by shrimps in the 2nd, 3rd, 4th, and 5th months was 0.04, 0.06, 0.17 and 0.19 mg.L-1.hr-1, respectively, and the average wet weight of shrimps was 1.8 ± 0.8, 6.8 ± 0.8, 15.8 ± 1.3 and 21.2 ± 1.3 g, respectively. The aeration rate by a paddle wheel was in the range 0.1–0.3 mg.L-1.hr-1. When all parameters were applied in the model, the predicted DO agreed with the observed DO with a correlation coefﬁ cient value of 0.9, which indicates that the assumption inherent in the DO budget processes was valid for the DO production and consumption in the pond.